Evaluation of properties of irreversible hydrocolloid impression materials mixed with disinfectant liquids - Arul Amalan; Kishore Ginjupalli; P Nagaraja Upadhya (Wolters Kluwer Medknow Publications, 2013)
Background: Addition of disinfectant to irreversible hydrocolloid impression materials can eliminate the disinfection step to avoid dimensional changes associated with it. The aim of the present study was to evaluate the effect of various disinfectant mixing liquids on the properties of commercially available irreversible hydrocolloid impression materials. Materials and Methods: Four commercially available irreversible hydrocolloid impression materials (Zelgan, Vignette, Tropicalgin, and Algitex) were mixed with disinfectant liquid containing chlorhexidine (0.1 and 0.2%) and sodium hypochlorite (0.1 and 0.5%). After mixing with disinfectant liquids, materials were evaluated for pH changes during gelation, gelation time, flow, gel strength, permanent deformation and detail reproduction. Results: Significant changes in gelation time were observed in irreversible hydrocolloid impression materials upon mixing with disinfectant liquids. In general, chlorhexidine increased the gelation time, whereas sodium hypochlorite reduced it. However, no significant changes in the flow were observed both with chlorhexidine and sodium hypochlorite. Gel strength was found to decrease when mixed with chlorhexidine, whereas an increase in gel strength was observed upon mixing with sodium hypochlorite. Permanent deformation of the most irreversible hydrocolloid impression materials was below the specification limit even after mixing with disinfectant liquids. Sodium hypochlorite significantly reduced the surface detail reproduction, whereas no change in detail reproduction was observed with chlorhexidine. Conclusion: Chlorhexidine solution can be used to mix irreversible hydrocolloid impression materials in regular dental practice as it did not significantly alter the properties. This may ensure effective disinfection of impressions.